IDEA JAR - Lehrhaupt, Adam; Piluttin, Deb (New York : Simon & Schuster Books for Young Readers, 2018)
What happens when the story ideas--from a bored Viking to a space robot--kept in a teacher's special jar escape and get rowdy?
"A Paula Wiseman Book" --Title page.
Interest age level: Ages 4-8.
Keywords: Storytelling -- Juvenile fiction; Imagination -- Juvenile fiction; Creative writing -- Juvenile fiction